Molecular classification of endometrial cancer: preliminary experience from a single Portuguese academic center - João Casanova; Ana G. da Costa; Ana Pestana Lopes; Ana Catarino; Mónica Nave; Ana Carla Sousa; Jorge Lima; Jorge Lima (Frontiers Media S.A., 2024)
BackgroundSince the seminal publication of the TCGA consortium in 2013, the molecular classification of endometrial cancer has been widely accepted as a new and powerful tool to better understand the natural history of this malignancy. Adoption of routine molecular classification around the world has been limited. We sought to demonstrate our initial experience in incorporating the four molecular subtypes for endometrioid carcinomas.MethodsThis was a retrospective analysis at a single center in Portugal. Molecular classification was determined using immunohistochemical staining for MMR and p53 and Sanger Sequencing to determine POLE mutation status as per published PROMISE method. Descriptive statistics were reported.Results20 patients with endometrioid histology were included. Median age of the cohort was 64 years (range 45-76). Median Body Mass Index (kg/m2) was 29.81 (range 21.3-43.1). In terms of tumor grading, 16 (80%) of the endometrial carcinomas of the cohort were low-grade (either grade 1 or grade 2). 16 (80%) of the cases were FIGO stage I. Regarding the molecular classification the tumors were classified as: MMRd [n = 6 (30%)]; p53 abn [n = 2 (10%)]; NSMP (n = 10 (50%)), POLE ultramut [n = 2 (10%)].ConclusionDespite the small sample size, we were able to show that molecular classification is feasible. To our knowledge this is the first cohort of endometroid endometrial carcinomas fully characterized according to the TCGA classification in Portugal, from one single center.